Adapalene and Doxorubicin Synergistically Promote Apoptosis of TNBC Cells by Hyperactivation of the ERK1/2 Pathway Through ROS Induction - Mehraj, Umar; Mir, Irfan Ahmad; Hussain, Mahboob ul; Alkhanani, Mustfa; Wani, Nissar Ahmad; Mir, Manzoor Ahmad (Frontiers in Oncology, 2022)
Doxorubicin is a commonly used chemotherapeutic agent to treat several malignancies, including aggressive tumors like triple-negative breast cancer. It has a limited therapeutic index owing to its extreme toxicity and the emergence of drug resistance. As a result, there is a pressing need to find innovative drugs that enhance the effectiveness of doxorubicin while minimizing its toxicity. The rationale of the present study is that combining emerging treatment agents or repurposed pharmaceuticals with doxorubicin might increase susceptibility to therapeutics and the subsequent establishment of improved pharmacological combinations for treating triple-negative breast cancer. Additionally, combined treatment will facilitate dosage reduction, reducing the toxicity associated with doxorubicin. Recently, the third-generation retinoid adapalene was reported as an effective anticancer agent in several malignancies. This study aimed to determine the anticancer activity of adapalene in TNBC cells and its effectiveness in combination with doxorubicin, and the mechanistic pathways in inhibiting tumorigenicity. Adapalene inhibits tumor cell growth and proliferation and acts synergistically with doxorubicin in inhibiting growth, colony formation, and migration of TNBC cells. Also, the combination of adapalene and doxorubicin enhanced the accumulation of reactive oxygen species triggering hyperphosphorylation of Erk1/2 and caspase-dependent apoptosis. Our results demonstrate that adapalene is a promising antitumor agent that may be used as a single agent or combined with present therapeutic regimens for TNBC treatment. Key Words: Breast cancer, TNBC, Doxorubicin, Adapalene, Chou-Talalay, Combination therapy, drug resistance